Effect of substrate media on virulence of Fusarium pallidoroseum: a potential bioherbicide for Parthenium management - HARRY C. EVENS*; J.O. HARVEY*, C. JEYALAKSHMI, SABITHA DORAISWAMY, V. VALLUVAPARIDASAN, R. RABINDRAN, (Indian Phytopathology, 2002)
Aggressiveness of the pathogen was influenced by the nutritional status of the substrate medium. F. pal/idoroseum, grown on Coon’s medium had greater biomass production with very good sporulation and was proved to be highly pathogenic on parthenium plant and its seed compared to the inoculum prepared from other media tried. The culture filtrate collected from the same also exerted maximum damage to the weed plant and its seed germination. Potato dextrose medium ranked next in respect of pathogenic behaviour. The aggressiveness of F. pallidoroseum was directly proportionate to its growth and sporulation of on culture media.